Guru Pendidikan Agama Islam sebagai Fasilitator dalam Ikhtiar Mewujudkan Motivasi Belajar Siswa SMP Negeri 3 Dompu Tahun 2020 - Firmansyah Firmansyah (Sekolah Tinggi Agama Islam (STAI) Al-Amin Dompu, 2020)
This research is descriptive qualitative field research. The data collection methods are observation, interview, documentation. While data analysis uses descriptive qualitative analysis techniques, namely describing and interpreting the data that has been obtained so that it describes the actual reality following existing phenomena. Research object at SMP Negeri 3 Dompu. The research objective was to determine the teacher's initiative as a facilitator in realizing the learning habits of students at SMP Negeri 3 Dompu? The results of the research show that the teacher's initiative as a facilitator in realizing the learning habits of SMP Negeri 3 Dompu students has been running, but not all of the eleven teachers' efforts as facilitators have been implemented properly. From observations and interviews, it was found that the two PAI teachers of SMP Negeri 3 Dompu had tried to carry out their efforts as facilitators such as trying to listen to the needs of students, being patient, facilitating learning activities, appreciating students, being positive, building an atmosphere of intimacy and personal communication and being equal in front of students. However, sometimes the teacher's attitude is still impatient, still occasionally trying to lecture students. The factors that hinder the efforts of teachers as facilitators in realizing the learning habits of students at SMP Negeri 3 Dompu? The inspirational factor is still not maximal. The teacher's effort as a facilitator is a factor in teacher habits in teaching where so far teachers have been accustomed to teaching with old patterns and this has strongly influenced the teacher's teaching style. Also, the teacher's mastery of the teacher's initiative theory as a facilitator is still not optimal.